Alcohol triggered bile acid disequilibrium by suppressing BSEP to sustain hepatocellular carcinoma progression. (1st April 2022) - Chen, Wenbo; Zhang, Qisong; Ding, Ming; Yao, Jingjing; Guo, Yajuan; Yan, Wenxin; Yu, Shaofang; Shen, Qinghong; Huang, Min; Zheng, Yaqiu; Lin, Yuefang; Wang, Ying; et al.
Abstract: Bile acids (BAs), the most important components of bile, attribute predominately to maintain metabolic homeostasis. In hepatocellular carcinoma (HCC) patients, the BAs homeostasis was seriously disturbed, especially in those patients with alcohol-intake history. However, whether alcohol consumption could promote HCC progression via influencing BAs homeostasis and the precise mechanism underlying are still unclear. In our study, by collecting HCC specimens from both alcohol-drinkers (n = 15) and non-alcohol drinkers (n = 22), we found that compared to non-alcohol intake HCC patients, BAs homeostasis was disturbed in HCC patients who drank alcohol. Furthermore, ethanol treatment was also found to promote HCC progression by markedly activating oncogenes (RAS, MYC, MET, and HER2), while remarkably suppressing tumor suppressor genes (BRCA2 and APC). We evaluated 14 key functional genes that maintain the homeostasis of BAs and found that either in alcohol-intake HCC patients (n = 15), or in ethanol-treated mice, BSEP, rate-limiting transporter governing excreting BAs from liver into bile duct, was remarkably decreased when exposed to alcohol. Moreover, by screening for changes in the epigenetic landscape of liver cancer cells exposed to alcohol, we strikingly found that histone methyltransferases (RBBP-5, Suv39h1, ASH2L, and SET7/9) were increased, and KMT3B, KMT4, and KMT7 gene expression was also elevated, while histone demethyltransferases (JARID1a, JARID1b, JARID1c) were decreased. In summary, we found that alcohol could trigger BAs disequilibrium to initiate and promote HCC progression. Our study provided a novel and supplementary mechanism to determine the important role of alcohol-intake in HCC development regarding from the perspective of BAs homeostasis. Graphical abstract: Image 1 Highlights: Drinking alcohol causes the imbalance of BAs homeostasis. Alcohol consumption decreased the expression of BSEP. The epigenetic landscape changed after alcohol treatment. BAs disorder can promote the occurrence and development of HCC.